Pemanfaatan Media Gamifikasi Pada Pembelajaran PAI Di Kelas XI SMA Ar-Rahman - Ruwaida, Siti (Journal of Sustainable Education, 2025)
This study aims to describe the utilization of Educaplay gamification media in the Islamic Religious Education (PAI) learning process for Grade XI students at SMA Ar-Rahman. The research employs a descriptive qualitative approach with data collection techniques including participatory observation, structured interviews with teachers and students, and documentation of learning activities. Data analysis was conducted narratively through the stages of data reduction, categorization, and interpretation to obtain a comprehensive overview of the implementation of the gamification media. The results of the study indicate that the use of Educaplay has a significant impact on improving the quality of PAI learning. This media helps increase students' learning motivation, strengthens active participation in classroom discussions, and encourages collaboration in group work. Furthermore, PAI material presented interactively through gamification facilitates students' understanding of religious values and their application in daily life. Although there are technical challenges such as internet access and teachers' adaptation to technology, these obstacles can be overcome through ongoing training and mentoring. Thus, the implementation of Educaplay as a gamification tool proves to be an innovative, effective, and relevant solution to meet the challenges of learning in the digital era.